Integrating palliative care into primary care for older people with multimorbid serious illness: a multinational qualitative cross-sectional study in Sub-Saharan Africa - Richard Harding; Maya Jane Bates; Lovemore Mupaza; Catherine J Evans; Kennedy Bashan Nkhoma; Adwoa Bemah Boamah Mensah; Dorothee van Breevoort; Dickson Dick Chifamba; Duncan Kwaitana; Modai Clement Mnenula; Edwina Beryl Addo Opare-Lokko (BMJ Public Health)
Background The WHO primary palliative care strategy states that palliative care is ‘an ethical responsibility of health systems’ and calls for integration of palliative care into public healthcare systems to achieve universal health coverage. We aimed to determine stakeholders’ perspectives on the necessary components of and considerations for a feasible and acceptable model of integrated palliative care and primary care for older people living with serious multimorbid illness in Sub-Saharan Africa.Methods We conducted a multicountry cross-sectional qualitative study in Ghana, Malawi and Zimbabwe. In-depth qualitative interviews were conducted with multimorbid older people and family caregivers. Focus groups were conducted with healthcare staff. Verbatim transcripts were subjected to inductive framework analysis to identify stakeholders’ needs and preferences for delivering and receiving palliative care in primary care facilities.Results The coding framework identified five main themes: (i) communication; (ii) coordination of care; (iii) impact of living with chronic illness; (iv) seeking healthcare; and (v) living with chronic illness: coping strategies and resources. The impact of multimorbid illness on older people was multidimensional, including pain and symptom control, catastrophic spending, social exclusion and limitations on activities of daily living. Specific challenges were identified in care pathways and delivery. Communication was sub-optimal, with lack of appropriate information and patient involvement.Conclusion Person-centred approaches are required to deliver palliative care to older multimorbid people in primary care settings. This study informs implementation of the WHO Healthy Ageing Policy intention to deliver person-centred primary palliative care and the WHO primary palliative care guidance.